2023
DOI: 10.1002/ece3.9927
|View full text |Cite
|
Sign up to set email alerts
|

Trophic transfer of polyunsaturated fatty acids across the aquatic–terrestrial interface: An experimental tritrophic food chain approach

Abstract: Aquatic and their adjacent terrestrial ecosystems are linked via the flux of organic and inorganic matter. Emergent aquatic insects are recognized as high-quality food for terrestrial predators, because they provide more physiologically relevant long-chain polyunsaturated fatty acids (PUFA) than terrestrial insects. The effects of dietary PUFA on terrestrial predators have been explored mainly in feeding trials conducted under controlled laboratory conditions, hampering the assessment of the ecological relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“…In line with our hypothesis, food quality explained most of the variation in the FA profile of chironomids. In fact, the differences between Spirulina and TetraMin, which served as food, were partially reflected in the FA profile of adult chironomids, while also suggesting that chironomids have the capacity to modify dietary FA (Goedkoop et al, 2007; Ohler, Schreiner, Martin‐Creuzburg, & Schäfer, et al, 2023; Strandberg et al, 2020). The capability to modify or preferentially retain certain dietary FAs was stronger when chironomids were fed with Spirulina, which could be explained by a greater discrepancy between chironomids' physiological demands and supply of this basal resource (Goedkoop et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with our hypothesis, food quality explained most of the variation in the FA profile of chironomids. In fact, the differences between Spirulina and TetraMin, which served as food, were partially reflected in the FA profile of adult chironomids, while also suggesting that chironomids have the capacity to modify dietary FA (Goedkoop et al, 2007; Ohler, Schreiner, Martin‐Creuzburg, & Schäfer, et al, 2023; Strandberg et al, 2020). The capability to modify or preferentially retain certain dietary FAs was stronger when chironomids were fed with Spirulina, which could be explained by a greater discrepancy between chironomids' physiological demands and supply of this basal resource (Goedkoop et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the energy transfer can be further amplified by the nutritional quality of (basal) resources. Similar to chironomids, spiders of the genus Tetragnatha have the capacity to modify dietary FAs (Mathieu‐Resuge et al, 2021; Ohler, Schreiner, Martin‐Creuzburg, & Schäfer, 2023), as indicated by the lower relative importance of the FA profile of the basal resource for the FA profile of spiders (Figure 4). However, the extent to which spiders use this ability depends largely on the dietary availability of certain physiologically important FAs because the modification of FAs is considered more energetically costly relative to their dietary uptake (Parrish, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids are important biomolecules transferred through aquatic and terrestrial food webs (Torres-Ruiz et al, 2007;Guo et al, 2017;Ohler et al, 2023). Consequently, the FA compositions of living organisms are inherently connected (Guo et al, 2016).…”
Section: The Trophic Transfer Of Fa From Algal Biofilm To Snailsmentioning
confidence: 99%